MEDIA AND CULTURAL IDENTITY IN THE AGE OF GLOBALIZATION: A SYSTEMATIC REVIEW (2019–2024) (Eureka Journal of Language, Culture & Social Change, 2025)
This systematic review explores how media globalization has influenced the construction, negotiation, and transformation of cultural identity in the digital era. Drawing from 42 peer-reviewed studies published between 2019 and 2024, this paper examines the dual role of media — both as a homogenizing global force and as a platform for cultural diversity. The review identifies three major themes: (1) cultural hybridization and global media flows; (2) identity resistance and localization; and (3) digital media’s role in shaping transnational identities. The findings reveal that while global media fosters intercultural understanding, it also triggers cultural anxieties and identity conflicts, especially among youth populations in developing nations.
Keywords: Globalization, Cultural Identity, Media Studies, Digital Communication, Cultural Hybridization